Fishery and population dynamics of Harpadon nehereus (Ham.) off the Saurashtra coast - Ghosh, Shubhadeep; Pillai, N G K; Dhokia, H K (Indian Journal of Fisheries, 2011)
The fishery and population dynamics of Bombay duck (Harpadon nehereus Ham.) from Nawabunder, Rajpara and Jaffrabad were studied for the period from 2003 to 2006. The average annual landings of Harpadon nehereus was 25,079 t, which contributed 31.12 % to the total dol net catches. The seasonal peak in catch was recorded during September – January and in May. The length–weight relationship showed that growth was isometric and there was no significant variation between the sexes. The overall sex ratio was 1:0.99 with gravid and ripe females encountered in most months with a peak during September – December. The length at first maturity of female was 20.2 cm. The growth parameters were estimated as L = 35.39 cm and K = 0.86 and the length attained at the end of 1, 2 and 3 years were 20.66 cm, 29.16 cm and 32.75 cm respectively. The length at first capture was 3.42 cm with recruitment occurring in most months of the year with a peak during February – June. The natural mortality, fishing mortality and total mortality were 1.52, 1.73 and 3.25 respectively and the exploitation ratio was 0.53. The maximum sustainable yield was 23,557 t, which was lower than the average annual catch indicating overexploitation of the species. The yield per recruit and biomass per recruit was 6.565 g and 3.79 g and increase in relative yield by 111.45 % would be obtained by decreasing the present level of fishing by 40 %.